231k views
2 votes
Solve the system.

x + 2y – 4z = 4
2x – y + 2z = 3
3x – 8z = -2

Enter answer as ordered triple.

(2,[?],[?])

Solve the system. x + 2y – 4z = 4 2x – y + 2z = 3 3x – 8z = -2 Enter answer as ordered-example-1

1 Answer

7 votes

From second equation :

2x - y + 2z = 3

z = (3 + y - 2x)/2

Putting value of z in equation 1 and 3, we get :

x + 2y - 4( 3 + y - 2x )/2 = 4

x + 2y - 2( 3 + y - 2x ) = 4

x + 2y - 6 -2y +4x = 4

5x = 10

x = 2

Putting value of x in third equation, we get :

8z = 3( 2 ) + 2

z = 1

Putting value of x and z in equation 2, we get :

y = 2( x+z) - 3

y = 2( 1 + 2) - 3

y = 3

Therefore, the answer as an ordered triple is ( 2, 1, 3 ).

User Ysap
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.